Tanggung Jawab Dinas Kependudukan dan Pencatatan Sipil Kabupaten Kupang dalam Menjamin Kepastian Hukum Bagi Pasangan Suami-Isteri yang Melangsungkan Perkawinan di Kecamatan Amarasi Timur - Bafelix Marlon Naitboho; Yohanes G. Tuba Helan; Detji K.E.R. Nuban (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The government is required to always be able to prosper the community it leads, but most people still lack participation in every government program or policy issued. As mentioned in Law Number 24 of 2013 concerning Population Administration, population documents are official documents issued by Implementing Agencies that have legal force as authentic evidence resulting from population registration and civil registration services. This study uses an empirical juridical method seen from norms or das sollen and an empirical approach, namely law as a social and cultural reality by taking primary data from the field in analyzing existing problems. Based on the results of research and discussion, it was found that the government in this case is still making efforts to pick up the ball in collaboration with traditional leaders and religious offices to socialize the importance of taking care of marriage certificates and collect data on couples who hold marriages in Kupang Regency and are required to issue marriage certificates after receiving marriage reports from the authorities